Diversity in Grain Amaranths and Relatives Distinguished by Genotyping by Sequencing (GBS) - Wu, Xingbo; Blair, Matthew W. (Frontiers in Plant Science, 2017)
The genotyping by sequencing (GBS) method has become a molecular marker technology of choice for many crop plants because of its simultaneous discovery and evaluation of a large number of single nucleotide polymorphisms (SNPs) and utility for germplasm characterization. Genome representation and complexity reduction are the basis for GBS fingerprinting and can vary by species based on genome size and other sequence characteristics. Grain amaranths are a set of three species that were domesticated in the New World to be high protein, pseudo-cereal grain crops. The goal of this research was to employ the GBS technique for diversity evaluation in grain amaranth accessions and close relatives from six Amaranthus species and determine genetic differences and similarities between groupings. A total of 10,668 SNPs were discovered in 94 amaranth accessions with ApeK1 complexity reduction and 10X genome coverage Illumina sequencing. The majority of the SNPs were species specific with 4,568 and 3,082 for the two grain amaranths originating in Central America Amaranthus cruentus and A. hypochondriacus and 3,284 found amongst both A. caudatus, originally domesticated in South America, and its close relative, A. quitensis. The distance matrix based on shared alleles provided information on the close relationships of the two cultivated Central American species with each other and of the wild and cultivated South American species with each other, as distinguished from the outgroup with two wild species, A. powellii and A. retroflexus. The GBS data also distinguished admixture between each pair of species and the geographical origins and seed colors of the accessions. The SNPs we discovered here can be used for marker development for future amaranth study.